2013
DOI: 10.1096/fj.13-240879
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide protein QTL mapping identifies human plasma kallikrein as a post‐translational regulator of serum uPAR levels

Abstract: The soluble cleaved urokinase plasminogen activator receptor (scuPAR) is a circulating protein detected in multiple diseases, including various cancers, cardiovascular disease, and kidney disease, where elevated levels of scuPAR have been associated with worsening prognosis and increased disease aggressiveness. We aimed to identify novel genetic and biomolecular mechanisms regulating scuPAR levels. Elevated serum scuPAR levels were identified in asthma (n=514) and chronic obstructive pulmonary disease (COPD; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 66 publications
5
46
5
Order By: Relevance
“…bronchial epithelial cells and observed increased proliferation as a result of this manipulation which was suggested to contribute to airway remodelling. (Portelli et al, 2014). This fits well with the observation of elevated levels of PLAUR in the airway epithelium in asthma patients (Stewart et al, 2012) and association of PLAUR levels with worsening prognosis and increased disease aggressiveness in other diseases such as cancer and COPD (Ivancso et al, 2013;Smith & Marshall, 2010).…”
Section: The Spatial Organization Of Chromosomes: Chromosome Conformasupporting
confidence: 83%
See 3 more Smart Citations
“…bronchial epithelial cells and observed increased proliferation as a result of this manipulation which was suggested to contribute to airway remodelling. (Portelli et al, 2014). This fits well with the observation of elevated levels of PLAUR in the airway epithelium in asthma patients (Stewart et al, 2012) and association of PLAUR levels with worsening prognosis and increased disease aggressiveness in other diseases such as cancer and COPD (Ivancso et al, 2013;Smith & Marshall, 2010).…”
Section: The Spatial Organization Of Chromosomes: Chromosome Conformasupporting
confidence: 83%
“…This approach identified a key SNP present in the promoter of human plasma kallikrein gene (KLKB1) as a determinant of suPAR protein levels, and subsequent biochemical analyses demonstrated that this SNP was an eQTL for KLKB1. We were able to show that KLKB1 subsequently cleaves uPAR from the surface of the cell providing a regulatory genetic posttranslational mechanism (Portelli et al, 2014). This study, using a protein eQTL approach, therefore identified a novel way whereby an asthma susceptibility gene can be modified by a genetically driven post-translational mechanism.…”
Section: Protein Eqtl Can Provide Novel Insight Beyond Cis and Trans mentioning
confidence: 88%
See 2 more Smart Citations
“…5,6 Migration of inflammatory cells from the bloodstream into tissues is an essential component of inflammation and the immune response against infection in which the uPAR/uPA system is directly involved. 7 During inflammatory stimulation, uPAR is cleaved from the cell surface by proteases to create the soluble form of the receptor, suPAR, which can be detected in blood, urine, and cerebrospinal fluid. 8 High suPAR levels were shown to be associated with an undesirable outcome in HIV infection, 9 active pulmonary tuberculosis, 10 bacterial meningitis, 8 and pneumococcal bacteremia, 11 suggesting that it may be a good biomarker of inflammation.…”
mentioning
confidence: 99%